Building Pancasila Civilization in Industrial Era 4.0 for Millennial Generation - A. Aco Agus (Program Pascasarjana Universitas Negeri Makassar, 2020)
Pancasila as the basis and ideology of the Indonesian state is a set of values that become a way of life for the Indonesian state, this condition ensures that the foundation of the state and the practice of national and state life must be based on the values contained in the Pancasila. The main challenges in grounding Pancasila in this globalization era are; decreased intensity of understanding of Pancasila in society, social exclusivism related to the swift flow of globalization so that it leads to a stronger tendency for identity politicization and social fragmentation based on SARA, decreased morality of millennial generation caused by the flow of information and technology that is not filtered properly as a result of the current industrial era 4.0. The efforts made in facing challenges in the millennial generation are fostering the spirit of nationalism, planting and practicing the values of Pancasila and using the internet wisely, building ideas and future visions of a strong young generation based on Pancasila morality.